2020
DOI: 10.1038/s41598-020-70493-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of plant-derived alkaloids, corydine and corydaline, as novel mu opioid receptor agonists

Abstract: Pain remains a key therapeutic area with intensive efforts directed toward finding effective and safer analgesics in light of the ongoing opioid crisis. Amongst the neurotransmitter systems involved in pain perception and modulation, the mu-opioid receptor (MOR), a G protein-coupled receptor, represents one of the most important targets for achieving effective pain relief. Most clinically used opioid analgesics are agonists to the MOR, but they can also cause severe side effects. Medicinal plants represent imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…The observation of plausible complexes of the MOR and the NOP receptor with KGNOP1 supports the multifunctional characteristics of KGNOP1. Our data also indicated the central contribution of the Dmt moiety for binding to the MOR through a charge interaction with D 3.32 , lipophilic contacts with Y 3.33 and M 3.36 , and a hydrogen bond to I 6.51 ( Figure 5 D), as critical residues for the binding of peptides, morphinans, and other chemotypes to the receptor [ 32 , 61 , 62 , 63 , 64 ]. For binding to the NOP receptor, the D 3.32 forms charge interactions with the basic Arg 8 and Lys 10 of KGNOP1 ( Figure 5 E).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The observation of plausible complexes of the MOR and the NOP receptor with KGNOP1 supports the multifunctional characteristics of KGNOP1. Our data also indicated the central contribution of the Dmt moiety for binding to the MOR through a charge interaction with D 3.32 , lipophilic contacts with Y 3.33 and M 3.36 , and a hydrogen bond to I 6.51 ( Figure 5 D), as critical residues for the binding of peptides, morphinans, and other chemotypes to the receptor [ 32 , 61 , 62 , 63 , 64 ]. For binding to the NOP receptor, the D 3.32 forms charge interactions with the basic Arg 8 and Lys 10 of KGNOP1 ( Figure 5 E).…”
Section: Discussionmentioning
confidence: 58%
“…In the antagonism studies, naltrexone (1 mg/kg, 2.6 µmol/kg) and SB-612111 (3 mg/kg, 6.6 µmol/kg) were injected s.c. 15 min and 30 min, respectively, before administration of KGNOP1 (1.22 µmol/kg, s.c.) to mice. Doses and pre-treatment times of the antagonists were selected based on previous research [ 61 , 66 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, effects of l -menthol and picrotoxin on [ 3 H]-EBOB binding were evaluated at 7 concentrations using the binding assay. Given that binding assays are usually performed in duplicate or triplicate, the assay of the present study was duplicated at each concentration as in previous studies ( Lever et al., 2017 ; Mollica et al., 2017 ; Kaserer et al., 2020 ), and the mean values were used to determine the IC 50 for each compound according to Eq. (3) , Eq.…”
Section: Methodsmentioning
confidence: 99%
“…To determine β-arrestin recruitment, F-81 and C-33 were evaluated for their potential stimulatory effects using the PathHunter enzyme complementation assay, with EM-1 as a reference [38,49]. Since in most studies reported in the introduction, β-arrestin 2 was used [19,[21][22][23]29], for easy comparison we decided to characterize this isoform, despite being the minority as compared to β-arrestin 1 in most cells, including neurons. The use of β-arrestin 2 is supported by its similarity in opioid receptor binding with β-arrestin 1 [37,50].…”
Section: Pharmacological Investigationsmentioning
confidence: 99%
“…Finally, the naturally occurring alkaloids corydine and corydaline were identified by virtual screening protocols (Figure 1). Ex-perimentally, these compounds acted as G protein-biased agonists to the MOP without inducing β-arrestin 2 recruitment upon receptor activation, and produced antinociception in mice after subcutaneous administration [29]. Despite the extremely promising preclinical in vivo data, TRV130 had underwhelming results in clinical trials [30], demonstrating only a trend toward reduced side effects, which were not significantly different from morphine.…”
Section: Introductionmentioning
confidence: 99%